Self-piercing riveting : properties, processes and applications - Chrysanthou, A.; Sun, X. (Woodhead Publishing series in welding and other joining technologies., 2014)
Due to its speed, low energy requirements, and the fact that it does not require a pre-drilled hole, the technique of self-piercing riveting (SPR) has been increasingly adopted by many industries as a high-speed mechanical fastening technique for the joining of sheet material components. Self-piercing riveting comprehensively reviews the process, equipment, and corrosion behaviour of self-piercing riveting, and also describes the process of evaluation and modelling of strength of self-piercing riveted joints, quality control methods and non-destructive testing. Part one provides an exte.